EVALUASI PENGENDALIAN AKUNTANSI ASET TETAP BERDASARKAN PERATURAN PEMERINTAH NOMOR 71 TAHUN 2010 TENTANG ASET TETAP PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI UTARA - Manorek, Devid; Morasa, Jenny; Sabijono, Harijanto (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Control of the Provincial Government Accounting is a systematic series of procedures organizers, equipment and other elements to realize the functions of accounting since the analysis of the transaction up to the financial reporting environment of the provincial government organizations. Fixed assets are tangible assets with a useful life of more than twelve ( 12 ) months for use in government activity or used by the general public . The purpose of this study was to evaluate control fixed asset accounting at the Department of Manpower and Transmigration of North Sulawesi Province . The results of this study indicate that accounting control of fixed assets at the Department of Manpower and Transmigration of North Sulawesi province in accordance with Government Regulation No. 71 Year 2010 . Keywords : Control, fixed Assets, evaluation.